2013
DOI: 10.1542/peds.2013-0721
|View full text |Cite
|
Sign up to set email alerts
|

Nonmedical Prescription Opioid and Sedative Use Among Adolescents in the Emergency Department

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Unintentional overdose and emergency department visits secondary to nonmedical use of prescription drugs are on the rise with peak age of onset in midadolescence for these risk behaviors. Also, risk behaviors, such as substance use and violence, tend to cluster. WHAT THIS STUDY ADDS:Approximately 1 in 10 adolescents or young adults using the emergency department endorse nonmedical prescription opioid or sedative use in the past year. Rates of current opioid or sedative prescriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 30 publications
3
33
0
Order By: Relevance
“…We observed that NMUPD was associated with DVV, although there was some variation in associations by type of victimization (sexual or physical DVV) and sex of the respondent. Our findings are consistent with some of the limited available literature, 11,27 although direct comparisons are difficult because assessment of DVV in our study varied substantially from that of other studies. For example, the few studies in the literature focused on NMUPD and DV among adolescent populations include both DVV and perpetration, 11,27 making it difficult to interpret findings from the perspective of developing targeted DV and substance use prevention efforts.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We observed that NMUPD was associated with DVV, although there was some variation in associations by type of victimization (sexual or physical DVV) and sex of the respondent. Our findings are consistent with some of the limited available literature, 11,27 although direct comparisons are difficult because assessment of DVV in our study varied substantially from that of other studies. For example, the few studies in the literature focused on NMUPD and DV among adolescent populations include both DVV and perpetration, 11,27 making it difficult to interpret findings from the perspective of developing targeted DV and substance use prevention efforts.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are consistent with some of the limited available literature, 11,27 although direct comparisons are difficult because assessment of DVV in our study varied substantially from that of other studies. For example, the few studies in the literature focused on NMUPD and DV among adolescent populations include both DVV and perpetration, 11,27 making it difficult to interpret findings from the perspective of developing targeted DV and substance use prevention efforts. Furthermore, in our study we differentiated associations by physical DVV only, sexual DVV only, and experiences with both physical and sexual DVV for both male and female adolescents.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Referral to treatment provides those identified as needing more extensive treatment with access to specialty care (SAMHSA, 2012). One study also raises the possibility that emergency room visits, for any reason, could become important occasions for detecting and addressing prescription drug problems among young people (Whiteside et al, 2013).…”
Section: Coalition Building For Prescription Drug Abuse Preventionmentioning
confidence: 99%